2008
DOI: 10.1093/jb/mvn014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Molecular Interaction between Tropoelastin and DANCE/Fibulin-5

Abstract: Fibulin-5 is believed to play an important role in the elastic fiber formation. The present experiments were carried out to characterize the molecular interaction between fibulin-5 and tropoelastin. Our data showed that the divalent cations of Ca(2+), Ba(2+) and Mg(2+) significantly enhanced the binding of fibulin-5 to tropoelastin. In addition, N-linked glycosylation of fibulin-5 does not require for the binding to tropoelastin. To address the fibulin-5 binding site on tropoelastin constructs containing, exon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 30 publications
3
32
0
1
Order By: Relevance
“…3), we examined whether oxidative modifications of TE alter the process of coacervation. Similar to previous studies (47) unoxidized TE coacervated at ϳ42°C (Fig. 4A).…”
Section: Oxidation Of Te Decreased the Optimal Coacervationsupporting
confidence: 90%
See 1 more Smart Citation
“…3), we examined whether oxidative modifications of TE alter the process of coacervation. Similar to previous studies (47) unoxidized TE coacervated at ϳ42°C (Fig. 4A).…”
Section: Oxidation Of Te Decreased the Optimal Coacervationsupporting
confidence: 90%
“…Hydrophobic amino acid residues (Tyr, Phe, Ile, or Leu) next to the Lys residues play a critical role in maintaining the optimal microenvironment for proper cross-linking (8,(47)(48)(49)(50)(51)(52) (Fig. 7, step 3).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there were no other proteins in this assay system that could reasonably bridge between tropoelastin and integrin ␣ V ␤ 3 . Interestingly the whole of the tropoelastin molecule has been shown to be necessary for fibulin-5-tropoelastin association (40), and so fibulin-5 should not associate with our cell adhesive peptide 36 and GRKRK. Therefore, it is unlikely that fibulin-5 will bind to this small section of tropoelastin, making it unlikely that fibulin-5 is acting as a bridging molecule for cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies and studies with transgenic mice showed that tropoelastin with altered or deleted sequences in this region is still capable of interacting with microfibrils to form an elastic fiber, although with abnormal cross-linking (7,42,43). How this region of tropoelastin facilitates fiber assembly is still unknown, although recent studies have identified binding sites for fibulin-4 and fibulin-5-, two proteins that facilitate elastin organization (44,45). Inactivation of these two fibulins in mice results in abnormal elastic fiber formation, and particularly relevant to our study, mutations in the human genes for fibulin-4 and fibulin-5 have been linked to an autosomal recessive form of cutis laxa (ARCL Type I) (46 -50).…”
Section: Discussionmentioning
confidence: 99%